Farmers, Agriculture and Rural Development in the Mekong Delta of VietNam - Nguyen, Ngoc De (Education publishing house, 2006)
A set of research papers on technology improvement and transformation based on the experiences of skilled farmers: an overview of rural and agricultural development in Vietnam; Farmer activities for rural and agricultural development; The relationship between the farmers and the support system; Conclusions and discussions on the characteristics of agriculture and rural society as well as the role of farmers in the Mekong region society.